Surgical treatment of nonunited fractures of the odontoid process, with special reference to occipitocervical fusion for unreducible atlantoaxial subluxation or instability - Dai, L. Y. (Springer-Verlag, 2000)
Fifty-seven consecutive patients treated surgically for nonunited fractures of the odontoid process were reviewed. All patients presented late, exhibiting neurological deficits subsequent to nonunion. Delay in presentation was between ¶6 and 120 months (mean 32 months) after the original injury, due to missed diagnosis or inappropriate management. Seven patients who were reduced in traction underwent a Gallie atlantoaxial fusion. In the remaining 50 patients who were unreducible, an occipitocervical arthrodesis was performed. They were followed up for a minimum of 2 years, except one who died from postoperative respiratory failure. All patients obtained a solid bony union, including two in whom nonunion occurred following atlantoaxial fusion, and occipitocervical fusion was added as a rescue. Thirty-eight patients achieved excellent neurological recovery, nine still had some disability, five retained their neurological deficits and two reported a deterioration. In two patients, a recurrence in a traumatic episode was experienced long after a resolution. Our findings demonstrate that occipitocervical arthrodesis is preferable for unreducible subluxation or instability of atlantoaxial articulation in nonunion of odontoid fractures.